Effect of Halal Label, Religiosity, Price and Product Quality on Purchase Decisions for Packaged Food and Beverages at Santri in Banyuwangi Regency - Muhammad Fikri Syaifulloh (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2024)
The Muslim population is the largest population in the world which will later reach an estimate of 2.049 billion people in 2020. The majority of the Indonesian population is Muslim, which greatly influences the developing culture regarding consumerization, one of which is regarding the consumption of foodstuffs. The following is an estimate of the world's Muslim population in 2020. In this study there are problems examined including the influence of halal labels on purchasing decisions , the influence of religiosity on purchasing decisions , the effect of price on purchasing decisions , the influence of quality on purchasing decisions of packaged food and beverages on students in Banyuwangi Regency. This study aims to determine the effect of halal labels on purchasing decisions , the effect of religiosity on purchasing decisions , the effect of price on purchasing decisions , the influence of quality on the purchasing decisions of packaged food and beverages in students in Banyuwangi Regency. This research uses quantitative methods. clarified as explanatory research , namelyresearch that aims to obtain an explanation of the relationship (causality) between several variables through hypothesis testing. The method used to determine the relationship between the dependent variable and the independent variable is multiple linear regression.